2022
DOI: 10.1155/2022/2075791
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Investigation on Immune‐Related Protein (Heat Shock Proteins and Metallothionein) Gene Expression Changes and Liver Histopathology in Cadmium‐Stressed Fish

Abstract: Heat shock proteins (HSP) are highly conserved in their structure and released in case of stress. Increased metallothionein (MT) synthesis is associated with increased capacity for binding heavy metals. Healthy juveniles of grass carp were exposed to sublethal dose (1.495 mg L-1) of cadmium for 28 days. Simultaneously, a control group was also run to compare difference of total RNA expression levels in cadmium-treated and control groups. The cadmium levels in the tissues of treated fish recorded were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…With the increase in Cd concentration, the degree of irreversible damage to the structure of fish liver cells also increases significantly, which mainly includes endoplasmic reticulum expansion, nuclear deformation, nuclear membrane mitochondrial swelling, distortion, granular cytoplasm, and cell edema and cavitation. When the liver tissue structure is destroyed, the detoxification ability of the liver is significantly reduced, which has an irreversible impact on growth, reproduction, and survival [ 17 , 95 , 96 ].…”
Section: Toxic Effects Of Cadmium Accumulation On Fishmentioning
confidence: 99%
“…With the increase in Cd concentration, the degree of irreversible damage to the structure of fish liver cells also increases significantly, which mainly includes endoplasmic reticulum expansion, nuclear deformation, nuclear membrane mitochondrial swelling, distortion, granular cytoplasm, and cell edema and cavitation. When the liver tissue structure is destroyed, the detoxification ability of the liver is significantly reduced, which has an irreversible impact on growth, reproduction, and survival [ 17 , 95 , 96 ].…”
Section: Toxic Effects Of Cadmium Accumulation On Fishmentioning
confidence: 99%
“…Several studies have shown that the expression of some genes under AHS is modified 36 , 70 72 , possibly through the interaction with small or long noncoding RNAs 20 24 . Therefore, the identification of key coding genes and their corresponding regulatory elements (i.e., lncRNA and miRNA) is critically important to reveal the causative factors associated with AHS in liver of chickens, as liver is extremely vulnerable under the influence of heat stress 73 , 74 . Structural similarity of lncRNA to mRNA 27 29 has allowed us to investigate both of them simultaneously using RNA-seq data.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%